Numerical Analysis of Experiments on Damage and Fracture Behavior of Differently Preloaded Aluminum Alloy Specimens - Michael Brünig; Moritz Zistl; Steffen Gerke (Metals, 2021)
A large amount of experimental studies have shown significant dependence of strength of ductile metals on stress state and stress history. These effects have to be taken into account in constitutive models and corresponding numerical analysis to be able to predict safety and lifetime of engineering structures in a realistic manner. In this context, the present paper deals with numerical analysis of the influence of the load path on damage and fracture behavior of aluminum alloys. A continuum damage model is discussed taking into account the effect of stress state and loading history on damage criteria and on evolution equations of damage strains. Experiments with the biaxially loaded H-specimen have been performed and different preloading histories have been taken into account. Evolution of strain fields is monitored by digital image correlation, and fracture modes are visualized by scanning electron microscopy (SEM). In addition, numerically predicted stress states are used to explain occurrence of different stress-state- and preloading-path-dependent localization behavior in critical specimens areas, as well as damage and fracture modes, revealed by SEM. The experiments with newly developed biaxially loaded specimens and corresponding numerical simulations show that the preloading history remarkably affects the occurrence of width and orientation of localized strain fields, as well as evolution of damage mechanisms and fracture modes. Therefore, characterization of materials must be based on an enhanced experimental program including biaxial tests with different loading histories. The observed damage and failure behavior can be predicted by the proposed continuum model taking into account stress-state-dependent damage criteria and damage strains.